Construction of Kedisan Pier to Increase Tourist Visits and Water Quality in Lake Batur, Bali - Agustina, Arik; Aprinica, Ni Putu Isha; Muliadiasa, I Ketut; Astina, Made Arya (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
Kedisan Pier gives a new feel of traveling in Batur, with a concept like a pier in South Korea, but also provides views of Lake Batur and Mount Batur simultaneously. Tourists not only visit restaurants, hot springs, hikes, and stay overnight but can also visit the Kedisan Pier Area. The increase in tourist visits influences the condition of water quality in Lake Batur. This study aims to determine the influence of the construction of Kedisan Pier on tourist visits and the quality of Lake Batur water. This study used a purposive sampling method; sampling was carried out at three points representing settlements and agriculture, water bodies/middle of lakes, and dock. The samples were tested for pH and temperature in the field and COD parameters in the laboratory. Furthermore, these three parameters are compared with Class 1 lake water quality standards in Government Regulation 22 of 2021. Based on the results, it is known that the pH and COD in the three locations exceed the class 1 water quality standard, which is 10 mg / L. pH in the range of 9.2 – 9.5. Increased COD concentration compared to the quality standard at point 1 by 127%; Point 2 is 82%, and Point 3 is 144%. Domestic activities cause the high pH and COD values at these three points—the highest COD value in the Kedisan Pier area. The construction of Kedisan Pier impacts the increasing number of tourists but also causes a decrease in Lake Batur's water quality. Based on this, human awareness is needed to increase tourism while maintaining the quality of waters for the future benefit of humans, flora, and fauna. In addition, further research needs to be carried out using other microbiological and chemical parameters to see the quality of Lake Batur waters.